2012
DOI: 10.1130/ges00753.1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Previous studies in the Yakataga foldthrust belt of the St. Elias orogen in southernAlaska have demonstrated high exhumation rates associated with alpine glaciation; however, these studies were conducted with only a rudimentary treatment of the actual structures responsible for the deformation that produced long-term uplift. We present results of detailed geologic mapping in two corridors across the onshore fold-thrust system: the Duktoth River transect just west of Cape Yakataga and the Icy Bay transect in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 67 publications
0
41
0
Order By: Relevance
“…Their use of glacial valley morphologies and comparison of the geology across the Bagley Ice Field valley leads to a provocative interpretation of ~50 km of dextral slip along with several kilometers of south-side-up displacement across the buried structure. They also present a 3D visualization of the structure in this area that is complementary to the models in Pavlis et al (2012), with additional interpretations of the geometry of the backstop from on June 9, 2014 geosphere.gsapubs.org Downloaded from their inference of the Bagley Ice Field valley structures. This novel use of ice fl ow and ice surface morphology presents new techniques for analyzing active structure in glaciated orogens, and may change interpretations of other orogens where ice covers active structures.…”
Section: Themed Issue Contentsmentioning
confidence: 97%
See 2 more Smart Citations
“…Their use of glacial valley morphologies and comparison of the geology across the Bagley Ice Field valley leads to a provocative interpretation of ~50 km of dextral slip along with several kilometers of south-side-up displacement across the buried structure. They also present a 3D visualization of the structure in this area that is complementary to the models in Pavlis et al (2012), with additional interpretations of the geometry of the backstop from on June 9, 2014 geosphere.gsapubs.org Downloaded from their inference of the Bagley Ice Field valley structures. This novel use of ice fl ow and ice surface morphology presents new techniques for analyzing active structure in glaciated orogens, and may change interpretations of other orogens where ice covers active structures.…”
Section: Themed Issue Contentsmentioning
confidence: 97%
“…Chapman et al (2012) describe the structural details and kinematics of the structures within the Samovar Hills, and show important details of the early deformation that occurred along the transpressional margin, prior to the arrival of the Yakutat terrane at the subduction-transform corner; they expand that work to a regional structural interpretation, including a synthesis of the structural history of this important plate corner collision in some of the most remote and rugged terrain in the world. Pavlis et al (2012) build on the work of Chapman et al (2012) with a systematic treatment of the structural geology to the west, including the area surrounding Icy Bay and a transect along the Duktoth River in the core of the fold and thrust belt. Pavlis et al evaluate the deformational history through a thorough description of the local geology in both the Icy Bay and Duktoth River transects, emphasizing the complexity and uncertainties in the eastern transect.…”
Section: Themed Issue Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…10-20 Ma (Enkelmann et al, 2008). Pavlis et al (2012) studied the exhumation in the St. Elias orogen and suggested that uplift due to thrust duplex structures may be related to shortening of the subducting Yakutat microplate. Due to the northwestward subduction of the Yakutat microplate underneath the Chugach Mountains, we suggest that the Yakutat microplate carried its cover beneath the margin and these sediments were underplating in late Neogene time, contributing to the observed uplift and exhumation event at 3-6 Ma (Enkelmann et al, 2008;Arkle, 2011).…”
Section: Underplating Of Sedimentsmentioning
confidence: 98%
“…Felsic igneous clasts may be derived from the Sanak-Baranoff plutons found dispersed along the southern Alaska margin (Sisson et al, 2003). The thick mud deposits documented in the cores may also reflect supply from the nearby St. Elias orogen that includes fold-and-thrust belts onshore and on the adjacent shelf north of Site U1419 (Worthington et al, 2008;Pavlis et al, 2012). The quartzofeldspathic sand beds are interpreted as potentially being derived by recycling of metasedimentary and sedimentary strata in the accretionary prism complex of the Chugach Range and the Neogene thrust belt of the Yakutat terrane (Plafker et al, 1994).…”
Section: Unit Imentioning
confidence: 99%